How to clean up your dirty data. - RICCIUTI, Mike (1993)
Describes two database quality software products - QDB/Analyze and Information Discovery System (IDS) - that can analyze database extracts and point to errors and inconsistencies in data using statistical analysis and knowledge-based systems technology.